(untitled) (Edad Media. Revista de Historia, 2024)
This study analyzes how, between 1420 and 1436, a cycle of conflict took place between the kingdoms of Castile, Aragon and Navarre, in which diplomacy and war alternated. We seek to analyze not only how diplomacy evolved but also the ways in which it was used by the royal powers throughout the different phases of the conflict.